Sterilisasi dan Induksi Daun Muda Durian (Durio zibethinus) Dalam Medium MS Dengan Penambahan Kinetin dan IAA Secara In Vitro - Supangkat, Gatot; Rineksane, Innaka Ageng; Pamuji, Kurniawati (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
A research  to study the sterilization   method  and application   of Kinetin  and IAA to induce the Durian  young  leaf (Durio zibethinus) in MS  medium   was conducted in Balai Benih Induk Hortikultura in Salaman  Magelang  district  of Central  Java  started  on September  until December 2003. The Laboratory experiment   was arranged  in two phases,  which were  the optimation  phase of sterilization   and  induction   phase.  At  the  first  phase,  the  sterilization method  used  was  the modification   of Mulya  (2001) method.  The modification   use of sterilant,  vitamin  C antioxidant, Alcohol  70 %, Benlate, Agrept,  Tween-20  and Betadine  were done to obtain  effectiveness   of the sterilization.  Explants  planted  then in MS medium  for two weeks. Contamination   time, percentage of contamination   and viabilitas  (percentage of living explants)  were observed  then.  At the second phase,  the treatments were arranged  in a 3 x 3 factorial  completely   randomized   design  (CRD)  to observed  the influence  of Kinetin  and IAA combination.   The concentration   of Kinetin  observed were 2, 4, and 6 mg/I, where  as the IAA concentration   were 0.5,  1.0, and  1.5 mg/I. All treatments were  repeated  three  times,  with three samples  on each  replication.   The percentage   of browning explants, percentage  of contaminated   explants,  site of  contamination   and percentage of explants live were observed  at the end of incubation. The results  showed that sterilization  of Durian young leaves explants  with 1  g/l deterjent  for 15 minutes  then by 2 g/l Benlate  and Agrept  for 10 minutes,  then by 1  g/200 mg Vitamin C, then by Alcohol  70 % for 1  minute, then by 20% Clorox,  then by 2 drip of Tween-20  for 10 minute and then by Betadine  decreased  the contamination down to 50 %, and this kind of sterilization  was relatively better than  the other  kinds.  Application   of growth  regulators   were  not  able  to induce  explants growth,  but stimulated  callus formation  at the cutting surface though,  in the application  of Kinetin 4 mg/1 + IAA 0,5 mg/I, Kinetin 4 mg/1 + IAA  1,5 mg/1, Kinetin  6 mg/I+  IAA 0,5  mg/1 and Kinetin 6 mg/l+IAA   1,0 mg/I.